Towards the feasibility of a landowner enterprise in the western Baviaanskloof : an external stakeholder analysis - Wiles, Kira Leigh Deborah (Rhodes University, Faculty of Commerce, Department of Management, 2014)
In May 2012, a meeting was held between various stakeholder representatives of the Western Baviaanskloof to discuss the concept of a proposed landowner-enterprise. This concept was put forward in response to a need for collaboration in the midst of economic, environmental and social issues at play in the Baviaanskloof. Owing to the conservation value and rapidly decreasing economic output of the land, a radical shift to sustainable land-use practices was called for by various stakeholders. Suggested as a vehicle to generate income for the local landowners through alternative sustainable land-uses, the proposed enterprise may aid in addressing this shift by use of a bottom-up approach. During the stakeholder meeting, it was requested by the representative landowners that a feasibility assessment be conducted on the concept of the proposed enterprise prior to establishment. As an integral part of this assessment, the researcher took on the task of investigating stakeholder reception to the enterprise by means of a stakeholder analysis. It was decided to limit this to three markets: water, carbon and tourism. The purpose of this research study is twofold, namely to: investigate stakeholder influence and their reception of the proposed enterprise using a stakeholder analysis; and also to identify and advise on the opportunities and constraints relating to stakeholders, thus contributing to determining the feasibility of the proposed enterprise. In achieving the purpose of this study, a systematic stakeholder analysis framework was constructed, based on existing theory. This was necessary because, although stakeholder analysis is commonly practiced, no study was found to provide a theoretically based framework for the purpose of feasibility in the initial stages of enterprise establishment. Thus the contribution of the study is also twofold, namely the practical outcome of determining stakeholder reception for feasibility, and a secondary outcome of constructing a stakeholder analysis framework. The stakeholder analysis framework is based on an interpretation of existing stakeholder theory, with the addition of four "relational indicators" "“ goals, intentions, relationships, and resources. These four indicators provide a link between theory and practice in gauging the two attributes of stakeholder influence "“ power and interest. Dealing with a number of stakeholder interests in a unique context, the study takes on a single network case study approach in the paradigm of phenomenology. To suit the complex nature of the study, semi-structured interviews with various stakeholder representatives were conducted, using groups or organisations as units of analysis. Drawing from the stakeholder analysis framework and overall purpose of the study, four research objectives were set. The first was to identify the proposed enterprise's legitimate key external stakeholders, based on the three markets: water, carbon and tourism; the second to describe, categorise and assess relative dyadic influence of the above stakeholders by gauging their power and interest; the third, to determine the stakeholder network influence and probable reception of the proposed enterprise; and the last to advise the landowners on any identified opportunities or constraints stakeholders might pose, and thus to contribute to determining feasibility. In addressing the first objective, 21 stakeholders were identified, 12 of whom were found to be key to the current investigation. These key stakeholders were: Gamtoos Irrigation Board (GIB), LivingLands, R3G, Rhodes Restoration Group, Eastern Cape Parks and Tourism Agency (ECPTA), Department of Water Affairs (DWA), Nelson Mandela Bay Metropolitan (NMBM), Saaimanshoek, South African National Biodiversity Institute (SANBI), Department of Economic Development, Environmental Affairs and Tourism (DEDEAT), Baviaans Tourism, and Baviaans Municipality. In applying the stakeholder analysis framework, ECPTA was categorised as the definitive (most influential) stakeholder to the enterprise, and DEDEAT, SANBI (through Working for Wetlands), Baviaans Tourism, GIB, and NMBM were categorised as pivotal (influential and active). In discerning stakeholder interest in the proposed enterprise, a number of emerging themes were found to affect the projected interest and behaviour of stakeholders, apart from their specified goals. Emerging themes included: tunnel visioning, internal disparity, individual/personality clashes, and misaligned interests. In addition to this, in interpreting stakeholder interest, specific intentions or agendas that might affect the interest shown towards the proposed enterprise were also taken into account. Five predominant intentions of stakeholders were identified as: implementing a stewardship programme, establishing a tourism association, establishing a water users' association, social development, and "the big vision". Findings on the final objective revealed a number of perceived opportunities and constraints relative to the feasibility of the enterprise. Three prime opportunities were identified as: partnerships with definitive and pivotal stakeholders, the possibility of tendering for implementer of the "Working for" programmes, and taking on the role of Tourism Association. The following potential constraints were also emphasised by participants: social aspects such as individuals and personalities, the incompatibility or non-existence of local market structures, and the need for external funding. With regard to stakeholder reception, most of the stakeholders, with the exception of NMBM and Saaimanshoek, responded positively to the idea of the enterprise. Overall, based on participant perceptions, the tourism market was found to be the most feasible the carbon market uncertain and a long-term possibility, and the water market the least feasible.
Keywords: Landowners -- South Africa -- Eastern Cape; Natural resources -- Co-management -- South Africa -- Eastern Cape; Land use -- Environmental aspects -- South Africa -- Eastern Cape; Land use -- Economic aspects -- South Africa -- Eastern Cape; Partnership -- South Africa -- Eastern Cape